Teaching Arabic Language (Extra Lessons) to The International Class at The State Islamic University of Indonesia | Ta'liim Al-Lughah Al-'Arabiyyah (Al-Duruus Al-Idhoofiyah) Li-Fashl Al-Dauly Al-Khash fii Al-Jaami'ah Al-Islaamiyyah Al-Hukuumiyyah Bi-Indonisiyya - Luluk Humairo Pimada; Nurul Aini; Zahrotul Isti’anah Marroh; Wildana Wargadinata (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
The international class in the Islamic Education study program establishes Arabic as a language of instruction in its implementation of learning, yet not all students have good competences in Arabic. Therefore, Arabic learning is an additional program that is taught outside of regular class hours to practice Arabic skills. Thus, this study explained the implementation of the Arabic learning process in the Islamic Education Study Program in the international class carried out for the first semester students. This study used descriptive qualitative. Collecting data in this study was done by conducting observation and documentation based on Miles and Huberman's theory. Data analysis used in this study was based on the process of collecting data, data reduction, and conclusion. The study result shows that Arabic learning becomes one of the programs that helps students to master Arabic. The implementation of learning using Arabic as the language of instruction can be understood by the students and it even facilitates the communication between the students and the teacher to create a more active learning atmosphere.